Association between statin use and immune-related adverse events in patients treated with immune checkpoint inhibitors: analysis of the FAERS database - Yang, Huaju; Huang, Rendong; Zhang, Ping; Liu, Yingtong; Liu, Zheran; He, Jiagang; Peng, Xingchen (Frontiers in Immunology, 2024)
Background: Understanding the risk relationship between statin use and immune-related adverse events (irAEs) in patients undergoing immune checkpoint inhibitors (ICIs) therapy is crucial for optimizing oncological management. Objective: This study aimed to investigate whether the use of statins increases the risk of irAEs in patients receiving ICI therapy. Methods: This study primarily utilized data from FAERS database. Multivariable logistic regression was the principal method of analysis, and the Benjamini-Hochberg procedure was employed to adjust for multiple hypothesis testing. Results: In a group of 145,214 patients undergoing ICI therapy, 9,339 reported using statin medications. Multivariable analysis indicated an increased risk of irAEs among statin users (OR 1.199, 95% CI: 1.141-1.261; FDR p < 0.001) in comparison to those not using statins. Notably, increased risks were observed particularly in patients diagnosed with lung, pancreatic, and renal cancers. The link between statin usage and increased irAEs risk remained consistent across various ICIs treatments. Conclusions: Statin medication usage is linked to an elevated probability of experiencing irAEs in patients enrolled in ICI therapy. In cancer patients receiving immune checkpoint inhibitors, careful consideration of statin use is essential to avoid potentially increased irAEs risk. These findings provide critical guidance for clinicians in developing treatment strategies that balance therapeutic efficacy and safety in oncological management.